Plants of Body Symbols in Tri Mandala Tenganan Pegringsingan Village, Karangasem (in Ethnobotany Learning Perspective) - Wijana, Nyoman; Rahmawati, Putu Indah; Nyoman Setiawan, Gusti Agung; Mulyadiharja, Sanusi (International Journal of Natural Science and Engineering, 2019)
This research aims to determine (1) the composition of body symbol plant species in each Tri Mandala in the village of Tenganan Pegiringsingan, (2) the coordinate points of reference for body symbol plant species in Tenganan Pegringsingan village, and (3) Plant species perspective body symbol in ethnobotany learning. The method used in this research is quadratic method, observation, and interview. Data were analyzed descriptively. The results of this study indicate (1) from 74 existing plant species, 14 plant species (19%) included in the body symbol plant category. (2) The distribution of body symbol species on Tri Mandala is categorized as having a wide, medium, or narrow distribution. (3) Coordinating points for the distribution of body symbol plant species ranging from 8°28,506 S 115° 33,994'E to 8°28,646 S 115°33,995'. (4) Plant species body symbols and their distribution to Tri Mandala have a good perspective to be packaged and implemented in ethnobotany learning.